Analisis Limpasan Permukaan Terhadap Saluran Drainase Ruas Jalan Ariate - Tanah Goyang Kabupaten Seram Bagian Barat - Maitimu, Anthoneta; Makatita, Afriani; Serang, Rudi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The Ariate - Tanah Goyang road section is a road section in Huamual District, West Seram Regency with a road length of 6 KM and a width of 4 M which was built with the aim of facilitating access for people to travel to the Regency Capital. This road section is a location where water puddles often occur when it rains due to the condition of the drainage channels which do not distribute water runoff properly because most of the channels do not have a drainage system. This is what causes problems with the road structure because it is unable to accommodate excessive standing water, causing damage to surface runoff. Based on the results of a 10-year return period calculation, the design rainfall was 195.884 mm, with a rainwater discharge on the Ariate - Tanah Goyang road section of 0.650 m3 and the planned cross-section type was a trapezoidal cross-section with a channel top width of 110 cm, channel bottom width of 61 cm and channel depth 80 cm. And the population growth rate (r) is 0.14% of the annual percentage for the projected population for the next 5 years is 1,309 people and the dirty water discharge in the drainage channel is 0.004 m3/hour/day.